Synthesis and biological evaluation of 2-alkyl-2-methoxymethyl-salvinorin ethers as selective κ-opioid receptor agonists. Issue 20 (15th October 2015) - Lee, David Y.W.; Deng, Gang; Ma, Zhongze; Xu, Wei; Yang, Lu; Liu, Jing; Dai, Ronghua; Liu-Chen, Lee-Yuan
Graphical abstract: Abstract: The synthesis of a new series of C-2-alkyl-2-methoxymethyl-salvinorin ethers and their binding affinities at κ -, μ -, and δ -opioid receptors are presented. We have developed a synthesis that enables installation of alkyl-substituents at C-2 while maintaining the integrity of the C-2 methoxymethyl ether and retaining κ -opioid receptor binding activity. Among these new compounds, 2-methyl-2-methoxymethyl-salvinorin ether (9a) is a potent full agonist at the κ receptor and shows comparable potency in Ki and EC50 with salvinorin A and U50488H. These C2-alkylated analogs have been identified as full κ agonists.